2017
DOI: 10.4236/health.2017.912119
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence and Obesity in Teenagers: An Analysis of the Last Ten Years of Studies

Abstract: Socially competent people using better strategies for solving interpersonal problems are more readily accepted by peers and valued by adults. Obese individuals, especially teenagers, have deficits in several social skills, which lead to damage to the relationships, self-esteem and in their valuation by social agents. This study examines how the literature of the last decade associates the components of social competence to obesity in adolescents. The research was carried out in electronic databases in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Some research indicates that social versus solitary gaming may make a difference: cooperative gaming is associated with prosocial behavior among university students (Greitemeyer & Cox, ) and social gamers spend more time on gaming (Eklund, ). Finally, as it has been reported that (a) high body mass index (BMI) in girls is associated with more gaming (Desai et al., ), and (b) that social competence correlates negatively with BMI (Sapienza, Schoen, & Fisberg, ), we also adjust for BMI.…”
Section: Why Gaming Might Impair Social Competencementioning
confidence: 99%
“…Some research indicates that social versus solitary gaming may make a difference: cooperative gaming is associated with prosocial behavior among university students (Greitemeyer & Cox, ) and social gamers spend more time on gaming (Eklund, ). Finally, as it has been reported that (a) high body mass index (BMI) in girls is associated with more gaming (Desai et al., ), and (b) that social competence correlates negatively with BMI (Sapienza, Schoen, & Fisberg, ), we also adjust for BMI.…”
Section: Why Gaming Might Impair Social Competencementioning
confidence: 99%
“…Obese individuals, especially teenagers, have deficits in social skills, which damage relationships, self-esteem, and their valuation by social agents. A study finding showed that the components of social competence were negatively associated with obesity, and most studies focused on self-esteem, the pattern of interaction with peers, and social relationships (Sapienza, Schoen, & Fisberg, 2017).…”
Section: Relationship Between the Respondents' Level Of Obesity And L...mentioning
confidence: 99%